EVALUATION OF SIDALIH IMPLEMENTATION USING PIECES FRAMEWORK - Yulianto, Yulianto; Huda, Miftahul (Jurnal Ilmu Komputer dan Agri-Informatika, 2024)
Various organizations including government (e-government) have used information technology to support services to the community. Indonesia is one of the major democracies and has implemented e-government in the field of democracy, commonly called e-democracy in the form of applications used to support the implementation of the 2024 election stages, one of which is SIDALIH. The preparation of the voters list is a very important stage to ensure the sovereign rights of citizens. The preparation of the voter list took a long time but until the last election in 2019 there were still various problems, including voters who had not been recorded in the DPT, fake voters, multiple voters, data disabilities, and abnormal data. Bawaslu's findings that 1,013,366 DPTs that were declared double were distributed in seventy-five districts/cities. Research on the use of SIDALIH in the 2024 election using the pieces framework. The variables in this study are performance, information and data, economics, control and security, efficiency, and service. The population in this study were all SIDALIH users in Kebumen Regency, while the sample was 320 from the organizers of the Kebumen Regency KPU. Data analysis was carried out using SmartPLS 3.0, including the outer model test, inner model including the R² test. The results showed that as many as 2 variables, namely performance and efficiency, had no influence on user satisfaction, and the variables of information and data, economics, control and security, service had a positive and significant influence on user satisfaction. Together the pieces framework has a contribution of 64.2% to user satisfaction, while 35.2% is influenced by other variables.